Centella asiatica increases hippocampal synaptic density and improves memory and executive function in aged mice - Gray, Nora E. (Brain Behav, 2018)
INTRODUCTION: Centella asiatica is a plant used for centuries to enhance memory. We have previously shown that a water extract of Centella asiatica (CAW) attenuates age‐related spatial memory deficits in mice and improves neuronal health. Yet the effect of CAW on other cognitive domains remains unexplored as does its mechanism of improving age‐related cognitive impairment. This study investigates the effects of CAW on a variety of cognitive tasks as well as on synaptic density and mitochondrial and antioxidant pathways. METHODS: Twenty‐month‐old CB6F1 mice were treated with CAW (2 mg/ml) in their drinking water for 2 weeks prior to behavioral testing. Learning, memory, and executive function were assessed using the novel object recognition task (NORT), object location memory task (OLM), and odor discrimination reversal learning (ODRL) test. Tissue was collected for Golgi analysis of spine density as well as assessment of mitochondrial, antioxidant, and synaptic proteins. RESULTS: CAW improved performance in all behavioral tests suggesting effects on hippocampal and cortical dependent memory as well as on prefrontal cortex mediated executive function. There was also an increase in synaptic density in the treated animals, which was accompanied by increased expression of the antioxidant response gene NRF2 as well as the mitochondrial marker porin. CONCLUSIONS: These data show that CAW can increase synaptic density as well as antioxidant and mitochondrial proteins and improve multiple facets of age‐related cognitive impairment. Because mitochondrial dysfunction and oxidative stress also accompany cognitive impairment in many pathological conditions this suggests a broad therapeutic utility of CAW.